Auditing Quality According To Artificial Intelligence: Applied Research on A Sample of Regulatory Bodies Working In The Federal Board of Supreme Audit (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Evolution Of Information Technology And The Use Of Computer Systems Led To Increase Attention To The Use Of Modern Techniques In The Auditing Process , As It Will Overcome Some Of The Human Shortcomings In The Exercise Of Professional Judgment, Then It Can Improve The Efficiency And Effectiveness Of The Audit Process, Where The New Audit Methodologies Espouse The Concept Of Risk Which Includes Strategic Dimension With Regard To The Capacity Of The Entity To Achieve Its Goals, Which Requires Auditors To Rely On Advanced Technology That Can Identify The Factors Which Prevent The Entity From Achieving Its Objectives. The Idea Of Research Is To Preparing An Electronic Program Fer All Audit Work From Planning Through Sampling And Documentation Of Working Papers To Get A Draft Of The Report And The Report Of The Evaluation Of The Supervisory Work Performance From The Hypothesis (That The Adoption Of Artificial Intelligence Technique In The Audit Process Stages Will Lead To The Success Of The Audit Function And Improving Its Quality), Artificial Intelligence Is Related To The Representation Of A Computer Model Of Area, An Then Retrieve And Develop As Well As It Is Compared With The Status And Events Of Research To Draw Helpful Conclusions.